The Expansion of a Company’s Activity and the Interests of Local Government Units and Financial Institutions - Janina Kotlińska; Grzegorz Kotliński (Barometr Regionalny, 2018)
The development of business operations requires coordination of many activities undertaken by entities from various sectors of the economy. Among them, financial institutions and local governments play a significant role. The implementation of development plans of enterprises requires coordination of cooperation with them. During this process, the interests of all parties are reconciled so that the implementation of the plans becomes possible and beneficial. The aim of the study is to identify potential barriers and to set out possible levels of cooperation between companies that declare their intention to expand and their financial institutions and local government authorities, competent for the aims of development plans. The study contains observations and considerations of the authors, supported by a literature query in the field of the undertaken topic.